(untitled) (Journal of Fiber Bioengineering and Informatics, 2024)
Sanitary napkins are indispensable personal care products for women. China is the largest market for feminine hygiene products in the world. China’s sanitary napkin industry is also large and stable, with annual sales reaching billions. However, despite the promise and potential of China’s sanitary napkin industry, there are few studies on it. In this study, anchored on industrial organisation theory and the structure-conduct-performance (SCP) paradigm, the characteristics of China’s sanitary napkin industry will be explored through three specific aspects: structure, conduct, and performance. Structure refers to the degree and nature of competition for products and services of an industry. Conduct is the market policies sellers adopt to achieve certain objectives, such as pricing and non-pricing. Performance is the outcomes reflecting the effects of market operation. The analysis will be conducted from the three aspects respectively. The results demonstrate that: (i) the market type of China’s sanitary napkin industry has shifted from competition to oligopoly V and has highly advertising-dependent product differentiation; (ii) cost-plus pricing conduct is adopted, and advertising sponsorship and channels construction have become a focus in this industry; (iii) the profit level of China’s sanitary napkin industry is relatively high but declining, and the industry scale structure needs to be improved. This study provides a theoretical perspective on the current standing of China’s sanitary napkin industry, which can assist the industry in growing steadily.